Skin‐Inspired Multifunctional Autonomic‐Intrinsic Conductive Self‐Healing Hydrogels with Pressure Sensitivity, Stretchability, and 3D Printability. Issue 31 (22nd June 2017) - Darabi, Mohammad Ali; Khosrozadeh, Ali; Mbeleck, Rene; Liu, Yuqing; Chang, Qiang; Jiang, Junzi; Cai, Jun; Wang, Quan; Luo, Gaoxing; Xing, Malcolm
Abstract : The advent of conductive self‐healing (CSH) hydrogels, a class of novel materials mimicking human skin, may change the trajectory of the industrial process because of their potential applications in soft robots, biomimetic prostheses, and health‐monitoring systems. Here, the development of a mechanically and electrically self‐healing hydrogel based on physically and chemically cross‐linked networks is reported. The autonomous intrinsic self‐healing of the hydrogel is attained through dynamic ionic interactions between carboxylic groups of poly(acrylic acid) and ferric ions. A covalent cross‐linking is used to support the mechanical structure of the hydrogel. Establishing a fair balance between the chemical and physical cross‐linking networks together with the conductive nanostructure of polypyrrole networks leads to a double network hydrogel with bulk conductivity, mechanical and electrical self‐healing properties (100% mechanical recovery in 2 min), ultrastretchability (1500%), and pressure sensitivity. The practical potential of CSH hydrogels is further revealed by their application in human motion detection and their 3D‐printing performance. Abstract : A double‐network hydrogel with conductivity, mechanical and electrical self‐healing properties, ultrastretchability, and pressure sensitivity is created. A 3D‐printed stretchable wireless sensor created from the hydrogel can detect pulse and muscle motions.